A long term study of the relations between erythemal UV-B irradiance, total ozone column, and aerosol optical depth at central Argentina. (September 2017) - Palancar, Gustavo G.; Olcese, Luis E.; Achad, Mariana; López, María Laura; Toselli, Beatriz M.
Highlights: Aerosols and ozone effects on UVER in Córdoba, Argentina were investigated. Single scattering albedo is an important parameter in the determination of the effects of aerosols. RAF due to ozone was in the range of 0.67 to 2.10 depending on AOD and SZA. The analogous effect due to aerosols was in the range of 0.06 to 0.27 depending on ozone and SZA. Abstract: Global ultraviolet-B irradiance (UV-B, 280–315 nm) measurements made at the campus of the University of Córdoba, Argentina were analyzed to quantify the effects of ozone and aerosols on surface UV-B erythemal irradiance (UVER). The measurements have been carried out with a YES Pyranometer during the period 2000–2013. The effect of ozone and aerosols has been quantified by means of the Radiation Amplification Factor (RAF) and by an aerosol factor (AF, analogous to RAF), respectively. The overall mean RAF under cloudless conditions was (1.2 ± 0.3) %, ranging from 0.67 to 2.10% depending on solar zenith angle (SZA) and on Aerosol Optical Depth (AOD). The RAF increased with the SZA with a clear trend. Similarly, the aerosol effect under almost-constant ozone and SZA showed that, on average, a 1% increase in AOD forced a decrease of (0.15 ± 0.04) % in the UVER, with a range of 0.06 to 0.27 and no defined trend as a function of the SZA. To analyze the effect of absorbing aerosols, an effective single scattering albedo (SSA) was determined by comparing the experimental UVER with calculations carried out with the TUV radiative transfer model.